Soil chemical properties under poplar-wheat agroforestry system in tarai lands of Uttarakhand - SOMAN, DIVYA; TEWARI, SALIL K.; AKHILRAJ, T.M.; RIYAZ, ARSHA (Journal of Soil and Water Conservation, 2026)
An investigation was carried out to study the chemical characteristics of soil under poplar-based agroforestry system at G.B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand during winter season of 2018. The poplar plants were about four and a half years old. Soil pH, soil electrical conductivity (EC), soil organic carbon (SOC) and contents of available macronutrients viz., N, P and K in surface soil (0–15 cm and 15–30 cm depth) were determined. Soil pH and EC were decreased whereas soil organic carbon, available nitrogen, phosphorous and potassium were higher under poplar- based agroforestry system as compared to open farming system. Highest nitrogen content was present under agroforestry system compared to open farming. At 0-15 cm the highest nitrogen measured was in treatment-1 plot (252.9 kg/ha) and lowest in treatment-8 plot (250.7 kg/ha). In open farming system the measured nitrogen content measured was 247.3 kg/ha. The maximum available phosphorus recorded was in treatment-2 plot (21.69 kg/ha) followed by treatment-4 plot (21.54 kg/ha). The agroforestry system recorded higher available potassium levels compared to the open farming system. Among the treatments, the treatment-5 plot showed the highest potassium content (219.6 kg/ha), followed by treatment-1 (219.3 kg/ha), while treatment-7 had the lowest (218.7 kg/ha); in contrast, the open farming system recorded 207.8 kg/ha. Therefore, the long-term adoption of poplar-based agroforestry system helps in improving the soil chemical properties as well as nutrient status.